SUPERIORITAS PEREMPUAN PADA IKLAN MEDIA DIGITAL YOUTUBE (Semiotika Kritis Travelio Versi Ringgo Family) - Dimas Rafi Santoso (2022)
This study aims to discuss the superiority of women in the Ringgo Family. To find out the symbols related to women's superiority and the meaning that refers to women's superiority, we use Julia Kristeva's semiotic theory, Paul Ricoeur's interpretation theory and Nancy Hartsock's stand point feminist theory. The method in this study uses qualitative methods, qualitative research methods are methods that have a foundation in the philosophy of postpositivism, are used to examine natural objects, researchers are the key instrument, data collection techniques are carried out by triangulation, data analysis is inductive/qualitative and emphasizes the meaning of on generalizations. This method is also used to obtain more in-depth and meaningful data. The final result of this research shows that there is an act of female superiority contained in the Travelio Ringgo Family the form of actions and traits that are more dominant in Sabai as a wife than Ringgo. The action is contained in 5 scenes from the total ad duration of 1:34 minutes. The element of feminism contained in the advertisement is postmodern feminism.